A model to promote the mental health of radiation therapy students throughout their training - Mokoena, Louisa; Henrico, Karien; du Plessis, Emmerentia (Health SA = SA Gesondheid, 2025)
BackgroundClinical placement constitutes an essential aspect of the radiation therapy (RT) undergraduate programme, but students have expressed that they often experience challenges during their training. There is limited guidance for RT lecturers and clinical tutors on how to support these students. Developing a model to promote their mental health during training was therefore essential.AimThis article outlines the development and evaluation process of a model aimed at promoting mental health support for RT students during their academic training programme.SettingThis model is intended for RT lecturers and clinical tutors involved in teaching RT students throughout their training.MethodsA qualitative, exploratory, descriptive, contextual and theory-generating study design was employed for the development of the model. The process of model development comprised four key steps: concept analysis, the formulation of relationship statements, model description and evaluation. The evaluation criteria used to assess the model included clarity, simplicity, generality, accessibility and significance.ResultsThe central concept identified was: ‘facilitation of a supportive learning environment’. The concept was defined, classified and placed into relationship statements leading to the development, description and evaluation of the model.ConclusionThe model can be used by RT lecturers and clinical tutors to promote mental health support for RT students during their academic training.ContributionThe contribution of the model is to strengthen the RT students’ mental health and empower them to develop their clinical skills in a supportive and nurturing learning environment.